2014
DOI: 10.1093/eurheartj/ehu353
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical factors in atherosclerosis: mechanisms and clinical implications

Abstract: Blood vessels are exposed to multiple mechanical forces that are exerted on the vessel wall (radial, circumferential and longitudinal forces) or on the endothelial surface (shear stress). The stresses and strains experienced by arteries influence the initiation of atherosclerotic lesions, which develop at regions of arteries that are exposed to complex blood flow. In addition, plaque progression and eventually plaque rupture is influenced by a complex interaction between biological and mechanical factors-mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
328
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 395 publications
(338 citation statements)
references
References 153 publications
4
328
0
6
Order By: Relevance
“…The underlying mechanism has remained elusive because ivabradine-targets have not been identified in vascular cells and ivabradine did not influence plasma lipid levels 11,13 . Given that ivabradine alters heart rate, stroke volume and coronary perfusion 22 , we tested the hypothesis that ivabradine may exert protective effects of arteries indirectly by altering hemodynamics which has been tightly linked to cardiovascular disease [15][16][17] . Our study demonstrated that ivabradine significantly altered flow in the murine aorta leading to enhanced WSS magnitude at both atheroprone and atheroprotected sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism has remained elusive because ivabradine-targets have not been identified in vascular cells and ivabradine did not influence plasma lipid levels 11,13 . Given that ivabradine alters heart rate, stroke volume and coronary perfusion 22 , we tested the hypothesis that ivabradine may exert protective effects of arteries indirectly by altering hemodynamics which has been tightly linked to cardiovascular disease [15][16][17] . Our study demonstrated that ivabradine significantly altered flow in the murine aorta leading to enhanced WSS magnitude at both atheroprone and atheroprotected sites.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although atherosclerosis is associated with systemic risk factors, such as hypercholesterolemia, it develops preferentially at branches and bends of the arterial tree that are exposed to complex patterns of blood flow 15 . Computational fluid dynamic (CFD) studies have demonstrated that the magnitude of WSS (time-averaged WSS (TAWSS) over the cardiac cycle) is lower at atherosclerosis-prone sites exposed to complex flow compared to regions that are protected 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…22 This might be the consequence of local differences in the mechanical forces exerted to the artery wall and the endothelium of the coronary vascular bed, causing local differences in plaque initiation and progression. 33 In contrast to the coronary arteries, both carotid arteries are exposed to similar blood flow patterns and mechanical stress. This might result in the same pattern of plaque development and progression.…”
mentioning
confidence: 99%
“…4 Suggested mechanisms include an increase in the magnitude and frequency of the mechanical stress imposed on the arterial wall, shortening of the atheroprotective diastolic period, and prolongation of endothelial exposure to atherogenic local hemodynamic factors. 5,6 The atherogenic microenvironment modulated by increased HR, in conjunction with the effect of systemic risk factors, promotes plaque formation and progression in atherosclerosis-prone regions.7 Reducing HR could potentially restrain the process of atherosclerosis which clearly relates to ischemia and, thus, angina.8 Ivabradine is a selective, pure HR-lowering agent that inhibits the If current in the sinoatrial node.9 Several studies have shown ivabradine to be noninferior to first-line antianginal agents, such as beta-blockers and calcium channel blockers, and superior to placebo.10-13 Ivabradine has a class IIa (level of evidence B) indication for the symptomatic treatment of chronic stable angina in patients intolerant to or inadequately controlled by beta-blockers. …”
mentioning
confidence: 99%
“…4 Suggested mechanisms include an increase in the magnitude and frequency of the mechanical stress imposed on the arterial wall, shortening of the atheroprotective diastolic period, and prolongation of endothelial exposure to atherogenic local hemodynamic factors. 5,6 The atherogenic microenvironment modulated by increased HR, in conjunction with the effect of systemic risk factors, promotes plaque formation and progression in atherosclerosis-prone regions. 7 Reducing HR could potentially restrain the process of atherosclerosis which clearly relates to ischemia and, thus, angina.…”
mentioning
confidence: 99%